Nickel Mining and Environmental Trade-Off in Raja Ampat Papua: A Conceptual Note on Legal and Policy - Werang, Nicolaus Petrus Likuwatan; Putri , Rizky Amalia; Werang, Maria Lusiana Florentin (Journal of Social and Policy Issues, 2026)
Nickel mining and the environmental trade-off in Raja Ampat, Papua, reveal an ambitious prospect for Indonesia’s national industry, driven by the global effects of minerals and the focus on the massive escalation of electric vehicle (EV) production. Moreover, this foundation presents a government dilemma, leaving too many legal and policy loopholes that could undermine resource governance. In addition, through qualitative descriptive approaches and content analysis, we identify issues that underpin a fragmented and selectively enforced legal regime characterised by weak environmental safeguards and inadequate community consultation processes. Interestingly, our research unexpectedly uncovers that the problem is poorly managed and neglects aspects of law and policy that we consider fundamental. As a call to action, this issue stresses the need for consistent resource governance reform for developing countries facing similar barriers and striving to achieve equity, sustainability, and local empowerment in extractive industry activities.